170k views
12 votes
Can someone explain to me how I can eliminate one of the variables to solve this equation for one of the variables?

Can someone explain to me how I can eliminate one of the variables to solve this equation-example-1

2 Answers

13 votes

Answer:

x = 1 and y = 4

Explanation:

Multiply the top equation by 7 on both sides, and then cancel it out:

7(5x + y) = 7(9)

35x + 7y = 63

Now use this equation to cancel out -7y on the second equation:

35x + 7y = 63

10x - 7y = -18

45x = 45

x = 1

Now that we have our x-value, we can plug it into one of our two original equations:

5(1) + y = 9

y = 4

User Davidsr
by
5.2k points
5 votes

Answer:

In the elimination method you either add or subtract the equations to get an equation in one variable. When the coefficients of one variable are opposites you add the equations to eliminate a variable and when the coefficients of one variable are equal you subtract the equations to eliminate a variable.

Explanation:

hope that helps! (:

User Ben Swinburne
by
4.9k points